Preparation of Lignocellulosic Nanofibrils from Bamboo Shoot Shells by the 3-Deep Eutectic Solvents Method and Performance Studies - Jianlong GUO; Jingjing DU; Song YANG; Qian ZHU; Jiayu GU; Jiagang GUO; Xiaowei WU; Jian JIANG (Shipin gongye ke-ji)
In this study, the 3-deep eutectic solvents (3-DES) system was designed based on the 2-deep eutectic solvents systems of choline chloride/glycerol and choline chloride/oxalic acid, respectively, and was combined with the high-pressure homogenization technique for the treatment of bamboo shoot shells. The effects of three metal ion chlorides on the structural features of lignocellulosic nanofibrils (LCNF) derived from bamboo shoot shells were investigated in various reaction systems. The results showed that the cellulose structure of the samples treated with choline chloride/glycerol/zinc chloride and choline chloride/oxalic acid/zinc chloride was destroyed, making them unsuitable for the preparation of LCNF. TEM analysis and particle size measurements indicated that the sample treated with the choline chloride/oxalic acid/ferric chloride system had the smallest particle size, measuring 58.77 nm. The dispersion of the sample treated with the choline chloride/glycerol/ferric chloride system was the best. When the third component was the same, the crystallinity of the sample treated with the choline chloride/oxalic acid system was higher than that of the sample prepared with the choline chloride/glycerol system, and the sample treated with the choline chloride/oxalic acid/aluminum chloride system exhibited the highest crystallinity. Furthermore, TGA analysis showed that the sample treated with the choline chloride/oxalic acid/ferric chloride system possessed the best thermal stability. In conclusion, this study found that treating bamboo shoot shells with 3-DES prepared by adding ferric chloride or aluminum chloride was an effective approach for the preparation of LCNF.